ASESMEN AUTENTIK DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Fitriah Khoirul Umamah; Moh. Sahlan (As-Sulthan Journal of Education, 2026)
The transformation of 21st-century education demands a paradigm shift in assessment from one focused on cognitive mastery to one capable of measuring students' comprehensive competencies, encompassing knowledge, attitudes, and skills. In Islamic Religious Education (PAI) learning, authentic assessment is crucial because learning objectives focus not only on mastering religious material but also on character building, internalizing Islamic values, and practicing religious teachings in daily life. However, PAI assessment practices are still dominated by conventional tests that tend to measure memorization skills, thus failing to comprehensively represent learning outcomes. This situation indicates a gap between the ideal goals of PAI learning and the evaluation practices implemented. Authentic assessment offers alternatives through various forms of assessment, such as projects, portfolios, observation of attitudes, and worship practices, which enable students to demonstrate real abilities in the context of everyday life. However, its implementation still faces various challenges, including limited teacher competence in designing authentic assignments, developing objective assessment rubrics, and systematically integrating assessment into the learning process. Therefore, a study of the concept, development of authentic tasks, design of assessment rubrics, and implementation of authentic assessment in Islamic Religious Education learning is important to support the creation of an evaluation system that is more meaningful, comprehensive, and oriented towards the holistic formation of student character.